Study on Effectiveness of Chakramarda (Cassia tora) Ghrit and Go-Ghrit in the Management of Parikartika (Fissure in Ano) - Alok Kumar Diwedi1,Alok Kumar Diwedi1, Kiran Khandare2 , Pooja Shrivastav3 Kiran Khandare2 , Pooja S (Indian Journal of Forensic Medicine & Toxicology, 2021)
The term Parikartika is used for the condition of Guda (anus) where cutting and burning pain occurs, also alongwith this pain occurs in anus, penis, umbilical region and neck of urinary bladder with cessation of flatus. In modernmedicine trend of the management depends on the type of the disease, e.g. in cases of acute variety with short historyof the problem can be treated on the conservative lines, which results in healing of almost all acute and majorityof chronic fissures. Priority must be placed normalization of bowel habits such that the passage of stool causes lesstrauma to anoderm. The addition of fiber to the diet to bulk up the stool, stool softener and adequate water intake arethe simple and helpful measures. In the present study, an effort was made to derive a standard and easily accessibletreatment for fissure-in-ano. Chakramarda is having vra?a shodhana and ropa?a properties which can help the Vra?a(ulcer) to heal rapidly. Its base is Ghrit which itself is having Samskaranuvarti (i.e. it enhances the properties of drug)and healing properties. Chakramarda Ghrit is economically beneficial by virtue of easily available ingredients anda time tested classical formulation. Hence, it was selected for the clinical evaluation in the present study. It provedto be significant in managing Fissure in ano, it reduced pain, itching, bleeding and promoted healing. Properties ofits chemical constituent’s probable mode of action can be derived that Chakramarda is efficient in healing any ulcerlike anal fissure.